COMMERCIAL RELATIONS BETWEEN RUSSIA AND SPAIN IN THE EARLY 19TH CENTURY - Volosyuk, O.V. (Vestnik Rossijskogo universiteta družby narodov. Seriâ Istoriâ Rossii (Print), 2017)
This article examines the development of trade relations between Russia and Spain during the reign of two Spanish kings: Charles IV and Ferdinand VII. The author’s attention is focused on the agency of diplomats, who made a big advance in the formation of trading relations between the two countries. The author concentrates on Ivan Muravyov-Apostol, the Russian ambassador to Spain (1802-1805), his Spanish partner Gaspar Maria de la Nava y Álvarez de Noroña (1802-1807), and on the consuls of Spain Antoni de Colombí (St. Petersburg) and Francisco de Baguer y Ribas (Odessa). Based on their reports, which are located in both Rus-sian and Spanish archives, it is possible to trace the dependence of commercial relations from the political situation in the world, established in Europe in the era of Napoleonic wars. Their information also allows revealing the main stages of development in trading during these years and the future, observe the merchantry on the Baltic Sea and in the area of the Black Sea. Ana-lyzing these materials, conclusions about the cause of diminishing of the commercial activity between Russia and Spain during the reign of Ferdinand VII can be made. The attention of the author is also paid to the conditions, which were established for the trade of Spain´s main export product to Russia - wine, and trading of grain through the area of the Black and Mediterranean Seas, which received special progress in the beginning of the 19th century.